The vanishing snow cover in Serra da Estrela: - Carla Mora; Gonçalo Vieira (Finisterra - Revista Portuguesa de Geografia, 2025)
This study investigates the evolution of snow cover in Serra da Estrela, the highest mountain in mainland Portugal, by integrating observational data from the Penhas Douradas meteorological station, remote sensing imagery, and climate model outputs. Results reveal a marked decline in the number of snow cover days at Penhas Douradas, dropping from an average of 53 days in the 1950s to 28 days in the 2010s, corresponding to an overall decrease of 5.4 days per decade. The rate of decline has slowed since the 1980s, as the station’s elevation still allows for snow during cold events but not for its sustained presence. To address the lack of observational data from higher elevations, we integrated multiple data sources – including low-elevation records, satellite imagery, and climate model projections — to reconstruct snow cover dynamics on the Torre Plateau since the late 19th century. Our reconstruction indicates a decrease from approximately 170 to 120 snow cover days in recent decades. Future projections under different climate scenarios suggest a continued and substantial reduction in snow cover, potentially reaching zero days by the end of the century under high-emission scenarios. Under the most extreme scenario, the Torre Plateau could experience snow conditions similar to those currently observed at 900 metres of elevation.